Does power shortage diminish firm CO2 emissions? evidence from Chinese listed firms - Li, Yushan; Ni, Chao; Shen, Bo; Zhao, Guoqin (Frontiers in Environmental Science, 2025)
The power shortages directly affect the production behavior of firms. The study utilizes a city-specific index of power shortage and a comprehensive database of listed firms in China to investigate the correlation between power shortages and firm CO2 emissions. Empirical results indicate a significant positive relationship between power shortages and firm CO2 emissions, alongside a noted decline in the extent of technological innovation among listed firms and a negative impact on their resource allocation. Further analysis shows that power shortage significantly contributes to the CO2 emissions of non-state-owned firms, non-heavily polluting firms and firms located in areas with high carbon-intensive energy use and fiscal expenditure pressure. These findings are robust across various sensitivity analyses and address concerns regarding endogeneity. Hence, policymakers are advised to take into account the influence of power shortages on CO2 emissions of listed firms, beyond their traditionally recognized adverse effects on economic operations. As frontrunners in China’s low-carbon transition, listed firms should strengthen risk resilience while driving technological innovation and resource optimization, thereby establishing operational paradigms for small and medium - sized firms to emulate.